The role of brimonidine tartrate gel in the treatment of rosacea - Jackson JM; Knuckles M; Minni JP; Johnson SM; Belasco KT (Dove Medical Press, 2015)
J Mark Jackson,1 Melissa Knuckles,2 John Paul Minni,3 Sandra Marchese Johnson,4, Kevin Tate Belasco5 1Division of Dermatology, University of Louisville, Louisville, KY, USA; 2PSC, Dermatology, Corbin, KY, USA; 3Waters Edge Dermatology, Stuart, FL, USA; 4Johnson Dermatology, Fort Smith, AR, USA; 5Blue Harbor Dermatology, Newport Beach, CA, USA Abstract: Rosacea is a chronic cutaneous condition with a prevalence rate ranging from 9.6% to 22% in recent studies. Facial erythema (transient and permanent) is considered a common denominator that is frequently observed in all subtypes of rosacea and is estimated to affect more than 40 million people worldwide. Brimonidine tartrate is a selective α2-adrenergic receptor agonist and is the first topical treatment approved for facial erythema of rosacea. Clinical trials have demonstrated that brimonidine tartrate provided significantly greater efficacy, compared to vehicle, for the treatment of moderate to severe erythema of rosacea. In addition, brimonidine tartrate has demonstrated a rapid onset of effect, duration of action throughout the day, and good safety profile in studies of up to 1 year. This review critically discusses the role of brimonidine tartrate for the treatment of facial erythema of rosacea by examining both clinical study data and real-world dermatologist experiences across a wide spectrum of treated patients, and concludes that it is a significant therapeutic option in the management of an unmet need of this chronic condition. Keywords: rosacea, brimonidine tartrate, erythema, adverse event